The Effects of ChatGPT Use and Self Regulated Learning on Students' Critical Thinking Skills: Evidence from the Faculty of Teacher Training and Education, Ekasakti University - Ayu Oktaviani; Caterina Lo; Serli Diovani Teza (The Future of Education Journal, 2026)
The rapid advancement of Artificial Intelligence (AI) has transformed higher education, particularly through the use of ChatGPT as a learning support tool. However, the extent to which AI ChatGPT usage and self-directed learning influence students' critical thinking skills remains unclear. Therefore, this study aimed to examine the effects of AI ChatGPT usage and self-directed learning on the critical thinking skills of students at the Faculty of Teacher Training and Education, Universitas Ekasakti. This study employed a quantitative approach using a survey method. The population consisted of 277 students, with 164 respondents selected through non-probability sampling using purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression with SPSS. The findings revealed that AI ChatGPT usage had a positive and significant effect on critical thinking skills (t = 2.086; p = 0.039 < 0.05), whereas self-directed learning had no significant effect (t = 1.381; p = 0.169 > 0.05). Simultaneously, AI ChatGPT usage and self-directed learning significantly influenced students' critical thinking skills (F = 3.244; p = 0.042 < 0.05). The coefficient of determination (R²) was 0.039, indicating that the independent variables explained 3.9% of the variance in critical thinking skills, while 96.1% was explained by other factors outside the scope of this study.